Usefulness of autologous serum for ocular surface lesions with uncertain progression. A clinical and imaging evaluation - Borobio, E (2021)
Objective: To determine the effectiveness of autologous serum rich in growth factors to repair ocular surface lesions which have uncertain progression with conventional treatment. Materials and methods: AForty-six (46) eyes with ocular surface disorders such as exposure keratopathy, keratopathy caused by dry eye syndrome, neurotrophic keratopathy and blunt eye injury were treated. The affected areas were the conjunctiva, cornea (epithelium, stroma) and sclera. Anatomical and functional evaluations were performed betweenMarch and December 2020 using Schirmer’s test, fluorescein eye stain and optical coherence tomography (OCT). Results: The symptoms improved in the following order: eye pain, foreign body sensation, blepharospasm, hyperemia and epiphora. Additionally, the lesions progressed favorably as follows: first, those of the conjunctiva and corneal epithelium; then, those of the corneal stroma; and, finally, those of the sclera. An average of 15 days was required for immediate ocular surface recovery and 21 days for late recovery. The lesions with total scleral thinning healed in about two months. Conclusions: The findings related to pain threshold, recovery time, scar tissue remodeling of the affected tissue and visual acuity improvement are promising and important. Using autologous serum rich in growth factors may be a therapeutic alternative for those lesions that are difficult to resolve with conventional treatment.